Penerapan Model Problem Based Learning untuk Meningkatkan Pemahaman Konsep IPA di SMP 7 Tandun - Masdinar, Masdinar; Riadi, Ahmad; Erliani, Erliani (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
A strong understanding of Natural Science (IPA) concepts is essential for middle school students to develop critical thinking and problem-solving skills. However, many students struggle to grasp scientific concepts due to traditional teaching methods that lack interactivity and student engagement. The Problem-Based Learning (PBL) model offers an innovative approach that emphasizes real-world problem-solving to enhance students’ conceptual understanding and critical thinking skills. This study aims to analyze the effectiveness of implementing the PBL model in improving students' comprehension of science concepts at SMP 7 Tandun. A quasi-experimental approach with a pretest-posttest design was employed. Data were collected through pre- and post-tests on science concept comprehension, classroom observations, and interviews with students and teachers. The findings indicate that implementing PBL positively impacts students' understanding of scientific concepts. Students became more engaged in discussions, better at connecting theories to real-world problems, and showed improvements in scientific problem-solving. Thus, the PBL model has been proven effective in enhancing students' understanding of science concepts at SMP 7 Tandun. The implementation of this model is recommended for broader adaptation to improve science education quality and foster students' critical thinking skills.